Everything to fight for: a brief history of Christianity and sectarian violence (Religious dialogue and cooperation, 2020)
This article recounts Christianity’s long history ofsectarian strife and division. The article discusses Christianity’sdiverse and global presence, describes the sectarian strife of itsearly years, narrates a short history of Christian sectarianism upto the present, and concludes with a reflection on reasons whysectarian tensions persist within the religion. The article endeavorsto assess why Christianity has struggled with sectarian tension, andposits that many of these tensions have arisen out of distinctionsand differences within language and culture. Christianity’s vastgeography helps to explain how a faith that was once ratherethnocentric blossomed to become the largest religion in the world,thus creating deep tensions linked to geographical and thereforecultural complexity. The Protestant Reformation brought aboutmany sectarian tensions that persist to the present. The modernecumenical movement has provided hope for a way forward,although no clear resolution is in sight. The article concludes witha discussion of various global examples where ecumenical activityand greater fellowship is emerging amongst sects once firmlydivided. Christian sectarian tension has cooled in Western Europelargely due to secularization tendencies, leaving Christians withlittle to fight for when it comes to religious belief.